Substructure and Signs of Planet Formation in the Disk of HD 169142. Issue Volume 8:Issue S299(2013) (6th January 2014) - Osorio, M.; Anglada, G.; Carrasco-González, C.; Torrelles, J. M.; D'Alessio, P.; Rodríguez, L. F.; Calvet, N.; Gómez, J. F.; Mayen-Gijon, J. M.; Dent, W. R. F.
Abstract: We carried out 7 mm VLA observations at very high angular resolution that reveal substructure and evidence of planet formation in the disk of HD 169142. Our observations, along with near-infrared polarimetric imaging, show that this disk has a ring of enhanced, asymmetric emission at a radius of ~25 AU from the central star. This ring, whose inner region appears devoid of emission, is surrounded by an annular gap in surface density in the ~30-70 AU range of radii. Several mechanisms have been invoked in the literature to explain this kind of gaps and cavities. Among them, one of the most interesting is the possibility that one or more planets in formation are creating these cavities. Since our 7 mm observations show a compact source lying in the 30-70 AU gap, we speculate that this compact source could be tracing dust emission associated with a possible protoplanet. We model the broad-band spectral energy distribution of the disk and we infer its physical structure. From this modeling we infer the presence of a small ( r ~ 0.7 AU) disk inside the central cavity, suggesting that the HD 169142 disk is in the pre-transitional disk phase.